Refugees and expellees in post-war Germany - Connor, Ian, Dr (Book collections on Project MUSE., 2007)
"The first study in English of the economic, social and political integration of the German refugees and expellees in post-war Germany, this book is based on extensive research in German archives and also incorporates the findings of numerous local and regional studies undertaken by German scholars. While its main focus is on the German Federal Republic, the book also provides coverage of the refugee problem in the German Democratic Republic." "This accessible book on a key aspect of post-war German history will be of particular interest to undergraduates of history, politics and German."--Jacket